Social Interaction of Students Based on Smartphone Addiction Level in Public High School 21 of Makassar - Rezki Yusfa Seftiani; Nurhaya Nurdin; Akbar Harisa; Hapsah Hapsah; Nuurhidayat Jafar (Indonesian Contemporary Nursing Journal, 2018)
Introduction: Smartphone is currently a tool for communications that is widely used by all people, especially among high school students. Excessive use of smartphone can lead to smartphone addiction. Someone who has a smartphone addiction have anti-social behavior towards his environment. This study aimed to describe of social interaction on the male and female students who have a smartphone addiction in SMA Negeri 21 Makassar. Method: This study design used is quantitative with descriptive survey. Selection of sample using cluster random sampling, total 95 respondent. Primary data obtained through questionnaires. Result: Based on the results of a study of 95 respondents, shows that respondents who experienced low-level smartphone addiction 19 people (28.8%) had a high social interaction, similar with respondents who experienced medium-level of smartphone addiction 43 people (65.2%) and high-level 4 people (6.1%) had a high social interaction. Conclusions: The study concluded that all levels of smartphone addiction has a high social interaction, not all respondents who use smartphones tend to be indifferent to his surroundings. They remain more comfortable communicating directly with the people closest. This research is expected can provide benefits that can be used as information specifically for students of SMAN 21 Makassar, and can improve socialization skills in the environment so that it can improve social interaction began to crushed